Lipolytic-screening of Bacillus genera as Biocontrol candidate In Coffee Plantation - Ema Ervina; Cristina Nugroho Ekowati; Sumardi Sumardi; Emantis Rosa (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
Problems in decreasing coffee production one of them caused by plant pests attack. Countermeasures using pesticides and disinfectants are not effective because they have long effects and ruining the environment also pest resistance. It is necessary to prevent a more environmentally friendly way by utilizing a natural enemy in the form of a microorganism, the genus Bacillus. Lipase can hydrolyze lipids so that it can be used to degrade lipid substrates that compile the body structure of pests and diseases. This research aims to detect the lipolytic activity of Bacillus isolates from coffee plantations. The results of this research obtained 3 isolates of Bacillus namely T1, T2, and T3 which have differences in cell configuration and variations in the location of endospores. Furthermore, Bacillus isolates were detected lipolytic activity by growing isolates on lipase selective medium. Isolates that have the largest lipolytic activity are T2 isolate codes with an average index of 6.01 and the lowest lipolytic activity, namely, isolate T1 codes with an average index of 4.58.